Analisa Potensi Zakat UMKM Mebel Melalui BAZNAS untuk Peningkatan Kesejahteraan Masyarakat Jepara - Fatchur Rohman; Aan Zainul Anwar; Subadriyah Subadriyah (Universitas Muhammadiyah Sidoarjo, 2017)
This study aims to determine the potential of zakah and issued UMKMcarving furniture and its effect on the welfare of the surrounding community through BAZNAS Jepara district, as well as deepen the knowledge and results of poverty modeling in Jepara district. Methods This research is a qualitative study of triangulation and method.. The result of this research is zakat potential in Jepara very big, especially from carving furniture sector where 91,27% carving furniture entrepreneur know and have understanding about zakahand counting zakah. The distribution of zakah UMKM carving furniture by 19.78% is channeled through Baznas Jepara this is because of the low role of UPZ at sub-district and village level. minimum potential of zakat top of UMKM furniture ukiritung Rp. 1.644.500.000, - and distributed to productive zakat with nominal Rp 25 Million/ recipient of working capital will be received as many as 65 recipients of zakah every year but this potential is not yet programmed by BAZNAS Jepara. In this researchthe awareness and knowledge of the society about zakah is very high, it needs to be socialized about zakah on the company, the preparation of existing financial instruments of zakah, and zakah can be as tax deductions.